2015
DOI: 10.5812/pedinfect.23516
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to Breast Feeding: A Review

Abstract: Context: Exclusive breast feeding, (EBF) protects young infants from infectious illnesses; various factors, including pacifier use, may adversely affect the initiation and duration of breast feeding. Evidence Acquisition: Mesh terms relating to EBF were used to search articles published in PubMed between 2000 and 2014. In addition to studies done outside Iran, articles from Iran addressing the issue of pacifier use in infants that had not been published in the PubMed, but were collected from Iranian journals, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Besides, maternal employment is a major factor in short-term breastfeeding patterns. 15 In fact, in our study, higher mixed feeding rates were observed in infants that have already started attending nurseries at six months because their mothers returned to work. Beyond that, 30% of these women were not entitled to a breastfeeding schedule, suggesting the importance of providing breastfeeding breaks by employers and providing access to these women to a private area where they may pump and store breastmilk.…”
Section: Socio-cultural Variablesmentioning
confidence: 43%
See 3 more Smart Citations
“…Besides, maternal employment is a major factor in short-term breastfeeding patterns. 15 In fact, in our study, higher mixed feeding rates were observed in infants that have already started attending nurseries at six months because their mothers returned to work. Beyond that, 30% of these women were not entitled to a breastfeeding schedule, suggesting the importance of providing breastfeeding breaks by employers and providing access to these women to a private area where they may pump and store breastmilk.…”
Section: Socio-cultural Variablesmentioning
confidence: 43%
“…Beyond that, 30% of these women were not entitled to a breastfeeding schedule, suggesting the importance of providing breastfeeding breaks by employers and providing access to these women to a private area where they may pump and store breastmilk. 15 EBF at three months old was more common in infants from mothers and fathers who are unable to communicate in Portuguese. Some reports describe exclusive breastfeeding adoption being more like a socio-cultural rather than technical process l. 16 There are some particularities about the African culture that may have a protective influence in EBF including grandmothers and other extended family members who frequently live together and have significant roles in childcare.…”
Section: Socio-cultural Variablesmentioning
confidence: 94%
See 2 more Smart Citations